Indicators Of Sustainable Tourism In Creative Cities: A Factor Analysis Of Chiang Mai (International Journal of Environmental Sciences, 2025)
This study investigates the indicators of sustainable creative cities and visitor management for tourism community development in Chiang Mai, a UNESCO Creative City of Crafts and Folk Art. The research seeks to answer the question: How can sustainable stakeholder, visitor, economic, cultural, and environmental management indicators be used to support effective community-based tourism? Using a quantitative approach and Exploratory Factor Analysis (EFA), data were collected from 570 stakeholders across Chiang Mai’s public, private, and people sectors. The findings reveal five significant factors, all with high reliability scores, providing a localized framework for sustainable tourism planning. This study contributes to bridging global sustainability frameworks (UNESCO, GSTC) with community-based tourism practices, offering policy implications for other creative cities globally.